Visitors’ opinions on the environmental protection in Shumen Plateau Nature Park from the negative anthropogenic impact of a nearby city, Bulgaria - Koynova, Teodora; Koleva, Vanya (Ecological Questions, 2021)
Parks are essential for the preservation and protection of wildlife, but human activity affects their functions. The objective of our study was to investigate visitors’ opinions on the environmental protection of Shumen Plateau Nature Park from the negative anthropogenic impact of a nearby city. Face-to-face interviews were conducted among summer visitors. The standardized Pearson correlation coefficient was calculated to determine the correlation between items questioned and demographic variables. The highest percentage of the informants were of the opinion that the Shumen Plateau Nature Park is a relatively clean place and a much cleaner green area compared to the parks in Shumen. According to most visitors, the high level of fine particulate matter in the air in the town of Shumen does not affect organisms that inhabit the Nature Park, soil and groundwater. The main pollutant of the Shumen Plateau Nature Park is garbage left by park visitors (88.97%), landfills in the park area (46.32%) and car traffic in the nearby town of Shumen (30.88%). The factor that has the most adverse effect on the biodiversity and ecological balance in the Nature Park are the visitors. Both visitors and inhabitants of the town of Shumen should be more responsible for the environment and the conservation of the Shumen Plateau Nature Park as a clean green area. Park visitors do not consider the town of Shumen as a source of negative anthropogenic impact on the Shumen Plateau Nature Park, but our previous studies show the opposite. This indicates a gap in the relationship between the scientific community and society that needs to be addressed. Close cooperation between scientists and journalists can contribute to the visitors’ opinions on the environmental protection in nature parks from the negative anthropogenic impact of nearby cities and towns and improve the effectiveness of the mass media.